“PENGARUH PIJAT PERINEUM MENGGUNAKAN MINYAK VCO (VIRGIN COCONUT OIL) TERHADAP LASERASI JALAN LAHIR PADA PERSALINAN NORMAL DI WILAYAH KERJA PUSKESMAS MRANGGEN I DEMAK” - Marida Isfaroh; Qomariyah Qomariyah; Maya Cobalt Angio (STIKES Telogorejo Semarang, 2022)
Birth canal laceration is the second cause of bleeding after uterine atony, which occurs in almost the first delivery and sometimes also in subsequent deliveries. In 2020 in the Maranggen 1 Health Center working area, there were 1013 deliveries, with 43.3% experiencing perineal lacerations. For this reason, an intervention is needed to prevent perineal lacerations, one of which is perineal massage which can increase perineal elasticity. The perineal massage can collaborate with VCO (Virgin Coconut Oil), where VCO contains variety of natural moisturizers and antioxidants that are important for skin care. In addition, it is relatively inexpensive and can be made at home. This study aims to determine the effectof perineal massage using VCO toward birth canal lacerations on mothers with normal delivery. This study used a quasi-experimental type using post-test only control group design. The study population was all pregnant women with gestational age starting at 37 weeks in the working area of the Mranggen I Health Center Demak. The sample was 60 respondents consisting of 30 control and 30 intervention groups. Meanwhile, the data was collected using observation. Data analysis consisted of univariate and bivariate analysis of the Chi-Square test technique. The results showed that perineal massage using VCO affected birth canal lacerations in normal delivery in the working area of the Mranggen 1 Health Center Demak (p-value 0.000 <0.05).